Teori simbol kesucian: analisis budaya etnik Sarawak - Magiman, Mohamad Maulana (Association for Researcher of Skills and Vocational Training, 2022)
Indigenous ethnic groups in Sarawak continue to perform rituals. This ritual was inherited from the Sarawak ethnic group through the form of performing arts for various ceremonies that lead to the almighty of God. The ritual is usually performed to seek blessings and well-being so the community is protected from various mishaps. However, the ritual's practice has evolved in response to anethnic group's lifestyle, and the influence of factors such as religious beliefs, development, and government policy. The component of the puritysymbol, which isthe core of Sarawak ethnic groups' ritual performance, will be discussed in this paper. However, the ritual offerings performed stillmaintain the reportoir's source and the same items used in each ritual performance. Data was collected using observational methods such as interviews with cultural practitioners, video recordings of presentations, and photographs. The existence of ritual performances revealed in each ethnic group in Sarawak is based on the factor of purity, which ensures that the rituals performed are accepted by God and, as a result, the well-being of each community is preserved. This documentation is crucial to ensure that the uniqueness of each ethnic group's rituals in Sarawak is sustained and preserved as a cultural treasure.